Integrated Transient Stability Analysis with Multi-Large-Scale Solar Photovoltaic in Distribution Network - Tran, Ngoc Thien Nam; Yang, Hong-Tzer; Duong, Minh Quan (Old Journal, 2017)
Using renewable energy sources (RES) to face energy shortages in the context of rising load demand is a central issue in national power system planning. [cite: 2] With low investment rates, rapid return on capital as well as many incentives from the government, solar energy is being more invested than other types of RES, as it can be seen as a rooftop and large-scale Photovoltaic (LSPV) system. [cite: 3] However, if the LSPV penetrates too much into the grid, it will weaken the stability of the system, especially when a fault occurs. [cite: 4] This paper aims to evaluate the transient stability of an actual distribution grid (DG) under different penetration levels of LSPV by ETAP software. [cite: 5] The frequency and voltage responses will be presented in the results along with the rotor angle variation of a conventional generator located near the LSPV. [cite: 6]